Anterior early repolarization pattern and T‐wave inversion in a healthy African‐Japanese athlete. Issue 6 (20th September 2019) - Sahashi, Yuki; Watanabe, Takatomo; Takasugi, Nobuhiro; Yanagimoto, Tatsuma Serge; Okura, Hiroyuki
Abstract : Precordial lead T‐wave inversion subsequent to early repolarization is thought to be a normal variant in African athletes and that additional testing is unnecessary. With the increasing number of foreign people living in and traveling to Asian countries, it is becoming crucial for Asian physicians to comprehend the abnormal ECG change in African athletes.